Fear of Recurrence in Chinese Cancer Patients: Prevalence, Correlates, and Network Analysis - Luo, Xian; Li, Wengao; Chen, Yu; Sun, Hengwen; Humphris, Gerry; Liu, Ting; Zhang, Jingying; Yang, Yuan; Zhang, Bin (Frontiers in Psychiatry, 2022)
Background Fear of cancer recurrence (FCR) is a significant issue for most cancer patients. Until now, a detailed investigation of the structure of FCR and the interaction among its constituent elements is lacking. This study aims to investigate the phenomenon of FCR by means of network analysis in Chinese cancer patients. Methods This is a multi-center, cross-sectional study that included 996 cancer patients from southern China. All participants were assessed by the 7-item Chinese version Fear of Cancer Recurrence Scale (FCR-7). Multivariate logistic regression, and network analyses were conducted. Central symptoms (nodes) in the FCR network were identified. Results Among the 996 patients, 543 (54.52%) reported moderate FCR, and 137 (13.76%) reported high FCR. Chemotherapy (OR = 2.954, P = 0.016), and childhood severe illness experience (OR = 2.331, P = 0.016) were positively associated with high FCR, while higher monthly income (OR = 0.403, P = 0.046) was negative associated with high FCR. The node #FCR2 (Worried/anxious about recurrence) was the most central node within the FCR network (Strength = 1.190), while node #FCR6 (Examining for physical signs) was the least central node (Strength = 0.373). The edge FCR1-FCR2 (“Afraid”-“Worried/anxious”) was the thickest and most saturated edge in the network. After controlling for age and gender, an almost identical network was obtained with respect to edges magnitude and strength. Conclusion Fear of recurrence is a frequently reported issue among Chinese cancer patients. Patients with chemotherapy and childhood severe illness experience were more vulnerable and should be particularly monitored. Compared to behavioral component (i.e., body checking, overscreening and overtreatment) and cognitive component (i.e., intrusions), emotional component (i.e., worry/anxious) is more central to identify FCR and might be potential targets for further interventions.